Dictators Walking the Mogadishu Line : How Men Become Monsters and Monsters Become Men - Larcom, Shaun; Sarr, Mare; Willems, Tim (World Bank, Washington, DC, 2016)
History offers many examples of dictators who worsened their behavior significantly over time (like Zimbabwe's Mugabe) as well as dictators who displayed remarkable improvements (like Rawlings of Ghana). The authors show that such mutations can result from rational behavior when the dictator's flow use of repression is complementary to his stock of wrongdoings: past wrongdoings then perpetuate further wrongdoings and the dictator can unintentionally get trapped in a repressive steady state where he himself suffers from ex-post regret. This then begs the question why such a dictator would ever choose to do wrong in the first place. The authors show that this can be explained from the dictator's uncertainty over his degree of impunity in relation to wrongdoing, which induces him to experiment along this dimension. This produces a setting where any individual rising to power can end up as either a moderate leader, or as a dreaded tyrant. Since derailment is accidental and accompanied by ex-post regret, increasing accountability can be in the interest of both the public and the dictator.